(untitled) (Research, Society and Development, 2022)
Facial appearance is an important feature both in the evolutionary context and in interpersonal relationships, the changes that occur in the development of the facial structure can cause anatomical disharmony, causing physiological and aesthetic adversities. Orthognathic surgery is a set of osteotomies techniques performed in the masticatory system with the aim of correcting discrepancies and restoring cranial and facial balance, treating dentofacial changes, promoting several positive results such as improved self-esteem, masticatory function, breathing and phonation. In this context, the objective was to discuss, through a narrative review of the literature, the importance of the correct indication of orthognathic surgery, promoting a better quality of life for patients, improving phonetics and providing facial harmony. The research includes a narrative review of the literature to synthesize evidence of the proposed theme in an article, based on previous work related to the theme, in order to facilitate the visualization of the results. The database was searched on Google academic, SciELO, Periódicos Capes. Through the survey of academic works, it was found that orthognathic surgery aims to rehabilitate patients with dento-skeletal discrepancies, restoring the balance of the face and skull, where the action of other health professionals is essential for the good development of the patient. The correct indication of the surgery will enable the success of the treatment, where the integration of the data collected in the anamnesis is necessary for a good planning.